Droplet‐Based Microfluidics Platform for the Synthesis of Single‐Atom Heterogeneous Catalysts. Issue 4 (4th April 2023) - Moragues, Thomas; Mitchell, Sharon; Faust Akl, Dario; Pérez-Ramírez, Javier; deMello, Andrew
Abstract : Microfluidic Synthesis of Single‐Atom Catalysts In article number 2200284, Andrew DeMello, Javier Pérez‐Ramírez, Sharon Mitchell, and co‐workers demonstrate a droplet‐based microfluidic approach enabling the short‐timescale and reproducible synthesis of diverse single‐atom catalysts to enhance their discovery and understanding.